Speech Analysis Classification and the Form of Commissive Speech Act Used in the Song "Beautiful Day" by Jermaine Edwards - Devy Yuniastuti Ramadhani (Enlighted Journal, 2024)
A speech act is an action performed when saying something. Without taking into account both the hearers and the speakers, speech acts cannot be properly comprehended. Speech acts are intended for real people, whose capacity for recognition places restrictions on the expressiveness of the lyrics. This research aimed to analyze the speech act classifications and the forms of commissive speech act used in Jermaine Edwards' song "Beautiful Day". This research used a qualitative method. The object of the research was Jermaine Edwards' song "Beautiful Day." The data were collected by using the observational method, followed by listening and note-taking techniques. Then the data were analyzed by using a descriptive approach to describe the types and forms of descriptive speech acts found in the song lyrics. The researcher used the theory of  Searle (1969) to analyze the speech act classifications and the forms of commissive speech acts. After analyzing the data, it was found five types of speech acts: representative, declarative, directive, expressive, and commissive. The forms of commissive speech act in the song "Beautiful Day" by Jermaine Edwards were promise, warn, and threat.